THE EFFECT OF ISOMETRIC HANDGRIP EXERCISE ON THE REDUCTION OF HIGH BLOOD PRESSURE IN HYPERTENSIVE PATIENTS AT THE KEBOMAS HEALTH CENTER - DICKY CHANDRA ARDIANSYAH; widiharti; Diah Jerita Eka Sari; Ernawati (Universitas Airlangga, 2025)
Introduction: Hypertension is a condition in which systolic blood pressure is more than 140 mmHg and diastolik blood pressure is more than 90 mmHg. The number of hypertension patients in Gresik Regency hospitals is 10,375 people. The intervention designed to reduce hypertension is Isometric Hangdrip Excercise, which functions to reduce cardiovascular reactivity to psychological factors, so that it can reduce systolic blood pressure by about 7 mmHg and diastolik by about 5 mmHg. Objectives of this study to analyze the effect of Isometric Handgrip Exercise on the reduction of blood pressure in hypertensive patients at the Kebomas Health Center. Method: The design of this study is Pre Experimental Design. This type of research is a quantitative research with the One Group Pretest – Posttest approach. The population in this study is 227 people with hypertension in the Kebomas Health Center area aged 46 – 65 years. Sampling was carried out using the Purposive Sampling method with a sample of 38 people. Result: The results of the Wilcoxon statistical test showed that the p-value of systolic blood pressure was 0.000 < the α value was 0.05 and the p-value of diastolik blood pressure was 0.008 < the α value was 0.05, meaning that there was an effect of Isometric Handgrip Exercise on the reduction of blood pressure in hypertensive patients at the Kebomas Health Center Conclusion: There is an effect of Isometric Handgrip Exercise on the reduction of blood pressure in hypertensive patients at the Kebomas Health Center